Variation of IgG N‐linked glycosylation profile in diabetic retinopathy. Issue 8 (18th February 2021) - Wu, Zhiyuan; Pan, Huiying; Liu, Di; Zhou, Di; Tao, Lixin; Zhang, Jie; Wang, Xiaonan; Li, Xia; Wang, Youxin; Wang, Wei; Guo, Xiuhua
Abstract: Background: The relationship of immunoglobulin G (IgG) glycosylation with diabetes and diabetic nephropathy has been reported, but its role in diabetic retinopathy (DR) remains unclear. We aimed to investigate and validate the association of IgG glycosylation with DR. Methods: We analyzed the IgG N‐linked glycosylation profile and primarily selected candidate glycans by lasso (least absolute shrinkage and selection operator) regression analysis in the discovery population. The findings were validated in the replication population using a binary logistics model. The association between the significant glycosylation panel and clinical features was illustrated with Spearman's coefficient. The results were confirmed by sensitivity analyses. Results: Among 16 selected glycan candidates using lasso, two IgG glycans (GP15, GP20) and two derived traits (IGP32, IGP54) were identified and validated to be significantly associated with DR ( P < .05), and the combined adjusted odds ratios (ORs) were 0.587, 0.613, 1.970, and 0.593, respectively. The glycosylation panel showed a weak correlation with clinical features, except for age. In addition, the results remained consistent when the subjects with prediabetes were excluded from the controls, and the adjusted ORs were 0.677, 0.738, 1.597, and 0.678 in the whole population. Furthermore, in the 1:3 rematched population, a significant association was observed, apart from GP20. Conclusions: The IgG glycosylation profile, reflecting an aging and pro‐inflammatory status, was significantly associated with DR. The variation in the IgG glycome deserves more attention in diabetic complications. Abstract : Highlights Immunoglobulin G glycosylation variation was associated with diabetic retinopathy (DR), in which GP15, GP20, and IGP54 showed a negative trend and IGP32 positivity. The significant glycosylation panel, reflecting an aging and pro‐inflammatory status, may capture a specific biological aspect and become a novel biomarker and drug target of DR. 摘要: 背景: 免疫球蛋白G(IgG)糖基化与糖尿病和糖尿病肾病的关联已有研究报道, 但其在糖尿病视网膜病变(DR)中发挥的作用仍不清楚。本研究拟探讨IgG糖基化水平与DR的关联。 方法: 本研究对IgG N连接糖基谱进行检测, 基于Lasso方法在第一个人群中初步筛选糖基指标。应用逻辑回归模型在第二个人群中对候选糖基指标进一步验证, 并进行敏感性分析。糖基指标与临床特征间的相关性采用spearman系数衡量。 结果: 在16个候选糖基指标中, 2个直接糖基峰(GP15和GP20)和2个衍生糖基峰(IGP32和IGP54)最终被验证与DR相关, 汇总后的校正比值比(OR)分别为0.587、0.613、1.970、0.593。除年龄外, 糖基指标与临床特征呈现较弱的相关性。将糖尿病前期人群从对照人群中剔除后, 结果保持一致, OR值变为0.677、0.738、1.597、0.678。在1:3匹配的人群中, 除GP20外, 其余糖基指标均与DR存在显著关联。 结论: 反映衰老状态和促炎功能的IgG糖基化改变与DR存在显著关联。IgG糖基化修饰在糖尿病并发症发生发展中发挥的作用应受到更多关注。